2021
DOI: 10.3389/fimmu.2021.641883
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites in the Tumor Microenvironment Reprogram Functions of Immune Effector Cells Through Epigenetic Modifications

Abstract: Cellular metabolism of both cancer and immune cells in the acidic, hypoxic, and nutrient-depleted tumor microenvironment (TME) has attracted increasing attention in recent years. Accumulating evidence has shown that cancer cells in TME could outcompete immune cells for nutrients and at the same time, producing inhibitory products that suppress immune effector cell functions. Recent progress revealed that metabolites in the TME could dysregulate gene expression patterns in the differentiation, proliferation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 150 publications
(165 reference statements)
1
18
0
Order By: Relevance
“…It is commonly recognized that the TME is immunosuppressive, which results from many regulatory factors, including low pH value, hypoxia, nutritional deficiency, metabolic pathways remodeling, inflammation, and others ( 24 , 25 ). Our focus in this work is to decipher the immune landscape of the HCC TME, facilitating clinical efficacy predictions of immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly recognized that the TME is immunosuppressive, which results from many regulatory factors, including low pH value, hypoxia, nutritional deficiency, metabolic pathways remodeling, inflammation, and others ( 24 , 25 ). Our focus in this work is to decipher the immune landscape of the HCC TME, facilitating clinical efficacy predictions of immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that epigenetic modifications and metabolism are highly interconnected (Saggese et al, 2020;Zheng et al, 2020;Li et al, 2021). Some metabolites (e.g., acetyl-coenzyme A (CoA), α-ketoglutarate, and nicotinamide adenine dinucleotide (NAD + )) are used as donors or cofactors for epigenetic modifications that regulate gene expression (Hosios and Vander Heiden, 2017;Palzer et al, 2018;Wang ZJ et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Secondy, tumor cells can shape and train the TME and ultimately help their survival and migration in an organism (44). Moreover, immune effector cells in TME are comprehensively reprogrammed as accomplices of tumor cells, which could protect cancer from immune destruction, subsequently evade immune surveillance and ultimately promote tumor progression and metastasis (17,(46)(47)(48)(49)(50)(51). Accumulating evidences showed that TME might be a main obstacle for effective cancer immunotherapy (52,53) and confers resistance to the immunotherapies (54).…”
Section: Introductionmentioning
confidence: 99%